2011
DOI: 10.1007/s00586-011-1826-2
|View full text |Cite
|
Sign up to set email alerts
|

Laminotomy in adults: technique and results

Abstract: The objective of this study was to describe step by step our surgical technique of laminotomy and analyze our series with regard to spinal deformities (risk and predisposing factors), postoperative pain and rate of postoperative contusions. Data regarding patients who underwent our technique of laminotomy (N = 40, mean follow-up: 52 ms) (N = 40) between 2002 and 2006 were retrospectively evaluated. The technique used is illustrated in depth. Chronic pain was present in 30% with a mean score of 3/10 cm (Graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…As mentioned previously, posterior laminectomy/laminotomy was the preferred approach. Laminectomy was used in 313 patients, while laminotomy was recently introduced in our department and used in 16 patients; five of them were reported in a previous series [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, posterior laminectomy/laminotomy was the preferred approach. Laminectomy was used in 313 patients, while laminotomy was recently introduced in our department and used in 16 patients; five of them were reported in a previous series [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Up until 2009, almost all patients were treated with a posterior laminectomy, associated with arterectomy and even partial pedicle resection when needed. From 2009 onwards, and just in selected cases, laminotomies were performed with reconstruction after surgical removal of the tumor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In a descriptive work by Ruggeri et al ., on the technique of laminotomy in forty patients over a period of 4 years, they acknowledged that a standardized procedure for the technique does not exist because of the various methods described in the literature and stated that laminotomy is not yet a standard approach to such pathologies of the spine despite their observation of satisfactory fusion of the osteo-ligamentous flap with the spine. [ 18 ] Compared with laminectomy previously carried out in another set of forty patients, their experience of postoperative kyphosis was far less than it was with the forty patients who had laminectomy. [ 18 ] Their work, however, included other pathologies of the spine apart from spine tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 11–13 In the last years, the literature suggested that laminotomy with laminoplasty may reduce this complication, even if the results are still controversial. 11,14–18 …”
Section: Introductionmentioning
confidence: 99%